Development of Articulate Storyline-Based Interactive Learning Multimedia for Grade VII Informatics Subjects at SMP Negeri 46 OKU - Indah Sari; Yamanto Isa; Heni Rita Susila (Universitas Trunodjoyo Madura, 2026)
This study aimed to develop interactive learning multimedia based on Articulate Storyline for seventh-grade Informatics subjects at SMP Negeri 46 OKU and to determine the feasibility of the developed media. The research employed the Research and Development (RD) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included material experts, instructional design experts, media experts, and seventh-grade students. Data collection techniques were conducted through observation, interviews, and questionnaires. The results showed that the developed learning multimedia obtained validation scores of 86% from material experts, 84% from instructional design experts, and 84% from media experts, all categorized as good. In addition, the student trial results obtained percentages of 80% in the one-to-one evaluation, 80% in the small group evaluation, and 83% in the field test, indicating that the developed multimedia was feasible for use in the learning process. Therefore, the interactive learning multimedia based on Articulate Storyline can be used as an effective and innovative learning medium to improve students’ interest, motivation, and understanding in Informatics learning.